Kessler’s syndrome: a challenge to humanity - Mariappan, Amrith; Crassidis, John L. (Frontiers in Space Technologies, 2023)
Kessler's Syndrome is a global phenomenon characterized by the presence of tens of millions of debris pieces of various sizes that disrupt satellite operations. This article delves into the potential outcomes of a Kessler's Syndrome occurrence and its implications on satellite operations. The potential threats posed by this scenario are discussed, including the implications of minimal to no satellite function on human impacts, including crashes and minimized or disrupted functions in essential utility services, as these sectors heavily rely on satellites such as GPS for navigation.In addition, we discuss how the loss of satellite communications could gradually or rapidly affect global affairs. As humans are a dominant force on Earth, their endangerment would reverberate throughout the ecological system, potentially leading to the demise of other species. It is crucial for policymakers and relevant stakeholders to recognize these implications and work towards safeguarding satellite communication to mitigate potential negative outcomes for humanity's well-being and progress. The recycling of space debris emerges as a promising and long-term sustainable solution to the mitigation of space debris. By repurposing decommissioned satellites and debris into useful materials to support other space missions, this recycling strategy presents a win-win scenario, promoting environmental sustainability and resource efficiency in space exploration.